Acromegaly Presenting with Resistant Acne Vulgaris - Fatema Abdulwahab Khamdan; Milaan A. Shah; Maryam Ahmed Khamdan; Eman Albasri (Karger Publishers, 2022)
Acne vulgaris is one of the most frequent skin diseases worldwide, triggered by multiple endogenous and exogenous factors. Hormones, particularly growth hormone (GH), insulin-like growth factor-1, insulin, CRH, and glucocorticoids, play a major role in the pathogenesis and exacerbation of acne. Excess GH seen in acromegalic patients may result in increased size and function of sweat glands and sebaceous glands, which may contribute to the patient's worsening acne and interfere with dermatologic treatment. Therefore, understanding the pathogenesis of acne will help in treating resistant acne by diagnosing and treating the underlying etiology using multidisciplinary treatment.